Translating AKHLAK Values into AI-Driven Innovation: Role of Cultural Agents in TelkomGroup's Digital Transformation - Sosidah Sosidah; Abdul Rohman; Andreas Cahya U.R.P. Saragih; Selamet Riyadi (PT. Anagata Sembagi Education, 2025)
This study explores how AKHLAK values-grounded cultural mechanisms at TelkomGroup transform AI adoption from passive compliance into committed, sustainable innovation. Employing an embedded single case study design with maximum variation sampling, this research engaged 15 informants selected via maximum variation sampling to ensure representation across business units (with varying adoption levels), generations, and organizational roles. In-depth interviews, non-participant observation, and document .cultural agents (Kipas Budaya) bridge socio-technical gaps findings: First, the configuration of Adaptive, Collaborative, and Competent values functions as a critical driver for AI assimilation, despite generational differences in how Gen Z/Y and Gen X/Baby Boomers perceive technological risks and opportunities Second, cultural agents (Kipas Budaya) bridge socio-technical gaps through three operational mechanisms: value-based narrative framing, credible peer modeling, and feedback mediation. Third, cross-unit analysis reveals that business units integrating AI infrastructure with robust cultural mechanisms demonstrate significantly higher Perceived Digitalization Impact (PDI) than those relying solely on technical readiness. Thus, successful digital innovation in State-Owned Enterprises requires activating core values as 'cultural infrastructure'—the critical mediator between structural factors and digitalization outcomes.